THE DIFFERENCE IN KNOWLEDGE BETWEEN PRIMIGRAVIDA AND MULTIGRAVIDA MOTHERS ABOUT THE DANGER SIGNS OF PREGNANCY AT SERIRIT 1 HEALTH CENTER - Wardana, Ketut Eka Larasati; Triguno, Yopita (Jurnal Medicare, 2022)
Background : Maternal Mortality Rate (MMR) is one of the efforts to assess the degree of public health. One of the problems associated with maternal mortality is the problem of pregnancy which should be avoided. Pregnancy problems can be detected early from the danger signs in pregnancy. One of the factors that influence mothers to know the danger signs of pregnancy is mother's knowledge. The purpose of this study was to determine the difference in knowledge between primigravida and multigravida mothers about the danger signs of pregnancy at the Seririt I Public Health Center. The research method was Comparative Study with a cross sectional approach. The population is primigravida and multigravida pregnant women at the Seririt I Health Center in 2021, with purposive sampling and obtaining a sample of 52 respondents. The research instrument used was a questionnaire. The results of the study were then analyzed by independent T-test. The results of the analysis showed that there was no difference in knowledge between primigravida and multigravida mothers about the danger signs of pregnancy at the Seririt 1 Public Health Center with a p-value of 0.000 and a p-value of 0.0160 so that the p-value was > 0.05. The conclusion is there is no difference in knowledge between primigravida and multigravida mothers about the danger signs of pregnancy.